2018
DOI: 10.7717/peerj.5997
|View full text |Cite
|
Sign up to set email alerts
|

Analyses of long non-coding RNA and mRNA profiling in the spleen of diarrheic piglets caused by Clostridium perfringens type C

Abstract: BackgroundClostridium perfringens (C. perfringens) type C is the most common bacteria causing piglet diarrheal disease and it greatly affects the economy of the global pig industry. The spleen is an important immune organ in mammals; it plays an irreplaceable role in resisting and eradicating pathogenic microorganisms. Based on different immune capacity in piglets, individuals display the resistance and susceptibility to diarrhea caused by C. perfringens type C. Recently, long non-coding RNA (lncRNA) and mRNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 61 publications
(65 reference statements)
1
14
0
Order By: Relevance
“…GADD45G may participate in the regulation of cell apoptosis by activating the MAPK signaling pathway [50]. Yan et al found that GADD45G was differentially expressed in the spleen tissue of piglets infected with C. perfringens [51]. In our study, GADD45G had the highest expression in the IS group, indicating this gene is closely related to intestinal damage and enterocyte death in the ileum of those piglets sensitive to C. perfringens type C.…”
Section: Discussionsupporting
confidence: 59%
“…GADD45G may participate in the regulation of cell apoptosis by activating the MAPK signaling pathway [50]. Yan et al found that GADD45G was differentially expressed in the spleen tissue of piglets infected with C. perfringens [51]. In our study, GADD45G had the highest expression in the IS group, indicating this gene is closely related to intestinal damage and enterocyte death in the ileum of those piglets sensitive to C. perfringens type C.…”
Section: Discussionsupporting
confidence: 59%
“…On the other hand, miRNAs are an abundant class of short (18–24 nucleotides) and highly conserved sequences of endogenous RNAs, which have been extensively studied in many species [ 14 ]. Previous studies have prospectively confirmed that ncRNAs (miRNAs and lncRNAs) were considered as crucial players in both humans and animals, and affect various biological functions [ 12 , 15 17 ]. Moreover, there is substantial evidence supporting that lncRNAs, acting as competing endogenous RNAs (ceRNAs), contribute to the regulation of cardiac fibrosis [ 18 ], muscle differentiation [ 19 ] and tumorigenesis [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the differentially expressed lncRNA (ALDBSSCG0000001631) involved in ileum immune response in CPID was found in porcine milk exosome. They also reported the potential lncRNA ( Yan et al, 2018a ) and circRNA ( Yan et al, 2018b ) functions in the spleen of diarrheic piglets caused by CPID. Liu et al (2018) and Chen et al (2019) revealed the potential role of lncRNA or circRNA in muscle and fat development in piglets.…”
Section: Discussionmentioning
confidence: 99%